Interval and Speed of Convergence on Iterative Methods - Adhikari, Iswarmani (Himalayan Physics, 2017)
The iterative method is a tool of solving the non-linear equations to get their approximate roots with some errors of tolerance. Repetition of the similar process is applied successively on such iterations to compute a sequence of increasingly accurate estimates of the roots. In this paper, the construction of an iterative method for solving an equation, its convergence and the determination of interval of convergence for the approximate choice of initial guess and the speed of convergence are highlighted. The Himalayan Physics Vol. 6 & 7, April 2017 (112-114)